STATE AND STRENGTH-DEFORMABILITY PROPERTIES OF THE MIRNY MINING AND PROCESSING PLANT (MPP) TECHNOGENIC TAILINGS DAM DEPOSITS AS A FACTOR OF DAM STABILITY - E. P. Dushkin; V. V. Akulova; A. A. Rybchenko; A. M. Yannikov (Геодинамика и тектонофизика)
The occurrence and development of exogeodynamic processes caused by liquefaction and fluidity of deposits that comprise the mine tailings dam may provoke emergency situations (breakthroughs). To prevent such situations, objects like these are covered by regular geomonitoring.The article presents the results of the study of the current state of the technogenic tailings dam deposits of the enrichment factory No.3 of the MPP (Mirny, Yakutia). Severe climatic, structural-geological and permafrost-hydrogeological conditions of the study area, as well as the thawed state of the technogenic strata (+0.5 to +3.1 °C) require to carry out a thorough control over the state of the dam in order to ensure its effective and safe operation.Studies of the material composition and properties of technogenic deposits were carried out based on the data on five drilled 31–58 m deep boreholes and sampling intervals. The granulometric and mineralogical compositions, as well as physical, physical-chemical and mechanical properties were determined according to standard methods using modern equipment (Analysette 22 NanoTec granulometric analyser, automated test complex ASIS).It has been found that the technogenic strata are layers of loose rock represented mainly by silty-clayey (sandy loam, loam and clay), less often by sandy material. Most of the clay varieties transform from solids to fluid-plastics. The most common lithological variety is silty loam, comprising ~40 % of the total volume sampled. The mineral composition of sediments is characterized by a high content of dolomite, calcite, quartz, serpentine and clay minerals. All clay deposits types have been found to have low strength (C=0.003–0.050 MPa, φ=3.9–15.7°) and high deformability (E=1.6–5.6 MPa). They also exhibit "dangerous" process-forming properties – plasticity, fluidity and flowability, which give rise to the development of exogenous geological processes (erosion, slumps, landslides, etc.), and consequently, influence the stability of the mine tailings dam.